2019
DOI: 10.7717/peerj.6120
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of non-magnetic and magnetic beads multiplex assay for assessment of Plasmodium falciparum antibodies

Abstract: BackgroundNew reagents have emerged allowing researchers to assess a growing number of vaccine-associated immune parameters. Multiplex immunoassay(s) are emerging as efficient high-throughput assays in malaria serology. Currently, commercial vendors market several bead reagents for cytometric bead assays (CBA) but relative performances are not well published. We have compared two types of bead-based multiplex assays to measure relative antibody levels to malarial antigens.MethodsAssays for the measurement of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…For most proteins the coupled beads were highly stable (11/16 tested over 9-months), with the MFI dropping for three proteins and increasing for two proteins. This is supported by previous research that has indicated the stability of protein-coupled beads [13], noting that the stability may vary by antigen [15].…”
supporting
confidence: 75%
See 2 more Smart Citations
“…For most proteins the coupled beads were highly stable (11/16 tested over 9-months), with the MFI dropping for three proteins and increasing for two proteins. This is supported by previous research that has indicated the stability of protein-coupled beads [13], noting that the stability may vary by antigen [15].…”
supporting
confidence: 75%
“…Comparison falciparum proteins [13]. This is despite different amounts of each protein being coupled to nonmagnetic versus magnetic beads ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall aim of this study was to establish a BBMA with biotinylated SAG1 and SAG2A as antigens for analyzing seroconversion resulting from T. gondii infection in humans. Magnetic beads have distinct advantages over nonmagnetic beads, including the ease of processing and higher bead recovery [8,44]. Since at the beginning of these studies the Sav-coated MagPlex ® microbeads were not commercially available, we custom-prepared them by chemical coupling of Sav to various bead regions (see Methods).…”
Section: Expression Puri Cation and Characterization Of Biotinylatedmentioning
confidence: 99%
“…The overall aim of this study was to establish a BBMA with biotinylated SAG1 and SAG2A as antigens for analyzing seroconversion resulting from T. gondii infection in humans. Magnetic beads have distinct advantages over non-magnetic beads, including the ease of processing and higher bead recovery [8,44].…”
Section: Bead-based Multiplex Assay With Biotinylated Sag1 and Sag2a mentioning
confidence: 99%